2019
DOI: 10.3991/ijep.v9i2.9947
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Factors related to Distributed Pair Programming

Abstract: This paper reports students’ perceptions and experiences attending an object-oriented programming course in which they developed software using the Distributed Pair Programming (DPP) technique. Pair programming (PP) is typically performed on one computer, involving two programmers working collaboratively on the same code or algorithm. DPP on the other hand is performed remotely allowing programmers to collaborate from separate locations. PP started in the software industry as a powerful way to train programmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…We also found how this changed over time. Our findings support the earlier research emphasizing the importance of and consensus over good tools for RPP [19,20]. Concerning RPP benefits, our study confirms that engineers pair program because they enjoy it [3], especially as an important mean for socialization while WFH, which goes beyond RPP for quality and efficacy [11] and is not much discussed in the existing literature.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
See 2 more Smart Citations
“…We also found how this changed over time. Our findings support the earlier research emphasizing the importance of and consensus over good tools for RPP [19,20]. Concerning RPP benefits, our study confirms that engineers pair program because they enjoy it [3], especially as an important mean for socialization while WFH, which goes beyond RPP for quality and efficacy [11] and is not much discussed in the existing literature.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 90%
“…In colocated PP, you work on the same code and frequently switch roles. In a distributed setting you need technology to support this [19]. Further, pairs also need to make voice and video calls and share screens during the coding activity.…”
Section: Remote Pair Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, social interactions lead to the students' reliance on sources other than the teachers instead of perceiving the teachers as the only source for acquiring skills and seeking suggestions, which reduces the tutors' work burden. Hsu et al [38] and Tsompanoudi et al [39] found that encouraging students to pair in a programming course was more effective for students engaging in high-level languages, leading to a higher percentage of students completing the course. Similarly, the distinctions between the learners who work "solo" and those working in pairs were made in a 2018 paper, contributing to the conclusion that programming knowledge, collaboration, and technical skills were further improved with a partnership [40].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Especificamente no contexto da programação pode-se observar uma metodologia de ensino, com características muito semelhantes a instrução por pares, essa metodologia é a Programação Em Pares, ou em inglês Pair-Programming (TSOMPANOUDI et al, 2019). …”
unclassified